2014
DOI: 10.1083/jcb.201405009
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelin homeostasis is required to form functional enzymatic domains at the trans-Golgi network

Abstract: Sphingomyelin-mediated organization of resident transmembrane proteins into specific membrane domains at the trans-Golgi network is necessary for normal enzymatic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 30 publications
5
59
0
Order By: Relevance
“…Our results show that Golgi cisternae curling starts already after 30 min of D-cer-C6 treatment, and that after 4 hr of treatment, virtually no flat stacks are observed (Figure 6C,D). In agreement with our previous analysis (van Galen et al, 2014), cisternae curling occurs towards the trans -Golgi cisternae/TGN, as monitored by the localization of specific late Golgi markers (Figure 6C). We extracted from these images the radius of flat cisternae, rflat=510±21 nm (average ± SEM; N = 22) and the radius of curling in the 4 hr D-cer-C6 treated Golgi cisternae, R=270±26 nm (average ± SEM; N = 14), which are in agreement with the condition of area conservation (Equation A2).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Our results show that Golgi cisternae curling starts already after 30 min of D-cer-C6 treatment, and that after 4 hr of treatment, virtually no flat stacks are observed (Figure 6C,D). In agreement with our previous analysis (van Galen et al, 2014), cisternae curling occurs towards the trans -Golgi cisternae/TGN, as monitored by the localization of specific late Golgi markers (Figure 6C). We extracted from these images the radius of flat cisternae, rflat=510±21 nm (average ± SEM; N = 22) and the radius of curling in the 4 hr D-cer-C6 treated Golgi cisternae, R=270±26 nm (average ± SEM; N = 14), which are in agreement with the condition of area conservation (Equation A2).…”
Section: Resultssupporting
confidence: 93%
“…Our previously (van Galen et al, 2014) and presently reported ultrastructural data shows that normal Golgi morphology is altered in cells where SM metabolism had been disrupted. Under those conditions, the original flat-like cisternae curl into a concentric stacked onion-like structure.…”
Section: Methodsmentioning
confidence: 58%
See 1 more Smart Citation
“…Van Galen and coll. recently showed modified organization of functional enzymatic domains and differential sorting of transmembrane proteins in the Trans-Golgi network after disruption of SM homeostasis [241]. …”
Section: Physiopathological Significancementioning
confidence: 99%
“…This postulate is supported by results obtained with D-ceramide-C6. This lipid derivative causes the disruption of cholesterol-and sphingomyelin-enriched domains at the Golgi (63), which is accompanied by a swelling of cisternae and alterations in N-glycosylation (63,66), both strikingly coincidental with impairments at the Golgi occurring after actin depolymerization and pharmacological V-ATPase inhibition (49,57,58). Importantly, D-ceramide-C6 treatment also caused Golgi and TGN pH alkalization, which also occurs after actin-depolymerizing toxins (49).…”
Section: Table 2 Reduction Of Golgi Membrane Lipid Order Increases Gomentioning
confidence: 99%